Growth-Promoting Potential of Rhizobacteria Isolated From Sugarcane - Santos, Roberta Mendes dos; Rigobelo, Everlon Cid (Frontiers in Sustainable Food Systems, 2021)
The search for plant growth-promoting rhizobacteria (PGPRs) addresses the ongoing need for new bioinoculants to be used on various agricultural crop species, including sugarcane. Bacterial strains were isolated from the rhizosphere of sugarcane plants and identified by sequencing the 16S ribosomal gene. The main indole acetic acid producers were Enterobacter sp. IP11, Enterobacter sp. IP14, and E. asburiae IP24. Achromobacter spanius IP23 presented the highest levels of cellulolytic activity and potassium solubilization. Bacillus thuringiensis IP21 and Staphylococcus saprophyticus IJ8 showed the highest levels of fixed nitrogen. The levels of calcium phosphate and aluminum phosphate in B. thuringiensis IP21 were notable, as this strain solubilized 481.00 and 39.33 mg of phosphorus mL−1, respectively; however, for Araxá apatite, the results for B. anthracis IP17 were notable (622.99 mg phosphorus mL−1), while for iron phosphate solubilization, Enterobacter sp. IP14, which solubilized 105.66 mg phosphorus mL−1 was notable. The B. thuringiensis IP21 and Enterobacter sp. IP11 isolates promoted the growth of the tallest sugarcane plants, inducing increases of 14.1 and 10.4% relative to the control plants, respectively. For shoot dry matter, root dry matter, and total dry matter, plants inoculated with Enterobacter sp. IP14, B. anthracis IP17, and A. spanius IP23 presented higher values than the controls. Furthermore, plants inoculated with B. thuringiensis IP21 presented higher root dry matter and total dry matter values, and those inoculated with Enterobacter sp. IP14 also presented higher total dry matter values. These results indicate that bacteria with the potential for use as future inoculants should be investigated since bacteria with plant growth-related characteristics may not impact growth promotion.